Analisis Perencanaan Kebutuhan Tenaga Pendidik Di SMPN 2 Batu Belah Kecamatan Siantan Timur Kabupaten Kepulauan Anambas - Rizadiliyawati, Rizadiliyawati; Aminudi Busro; Dahrani; Afriza, Afriza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The purpose of this study was to analyze the Analysis of Teacher Needs Planning at SMPN 2 Batu Belah, Siantan Timur District, Anambas Islands Regency. The type of research conducted was mini research, data collection through interviews and observations. Planning for teacher needs at SMPN 2 Batu Belah is crucial to maintain the quality of education. The first problem shows that the shortage of teachers in this school is caused by the number of students studying, limited budget, and lack of teachers with appropriate backgrounds, especially in science and English subjects. Geographical factors and uneven teacher quality affect teacher planning. To overcome this, long-term planning is needed with data-based needs analysis, improving teacher competence through training, and utilizing technology in learning. Collaboration with universities and local government support is essential to ensure effective and sustainable teacher planning.